2016
DOI: 10.4238/gmr.15028310
|View full text |Cite
|
Sign up to set email alerts
|

Controversial results of therapy with mesenchymal stem cells in the acute phase of canine distemper disease

Abstract: ABSTRACT. Distemper disease is an infectious disease reported in several species of domestic and wild carnivores. The high mortality rate of animals infected with canine distemper virus (CDV) treated with currently available therapies has driven the study of new efficacious treatments. Mesenchymal stem cell (MSC)-based therapy is a promising therapeutic option for many degenerative, hereditary, and inflammatory diseases. Therefore, the aim of this study was to characterize stem cells derived from the canine fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…the high rate of virus replication in the lymphoid tissues of dogs leads to lymphopenia from transient depletion of CD21+ B, CD8+ T, and CD4+ T cells (Carvalho et al, 2012), profound immunosuppression due to leukocyte necrosis and apoptosis (Carvalho et al, 2012;Beineke et al, 2015),and inhibition of the responses of interferon and cytokines secreted by the lymphoid cells (Greene and Vandevelde, 2012) and that, therefore, this immunodepression could be potentiated by exogenous use of MSC. This information may explain the success of the treatment that we applied when confronted with the data of Pinheiro et al (2016) who observed a high mortality rate (67%) among their patients; they used dogs that already presented severe respiratory and gastric clinical signs, in addition to neurological manifestations typical of the acute phase of distemper.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…the high rate of virus replication in the lymphoid tissues of dogs leads to lymphopenia from transient depletion of CD21+ B, CD8+ T, and CD4+ T cells (Carvalho et al, 2012), profound immunosuppression due to leukocyte necrosis and apoptosis (Carvalho et al, 2012;Beineke et al, 2015),and inhibition of the responses of interferon and cytokines secreted by the lymphoid cells (Greene and Vandevelde, 2012) and that, therefore, this immunodepression could be potentiated by exogenous use of MSC. This information may explain the success of the treatment that we applied when confronted with the data of Pinheiro et al (2016) who observed a high mortality rate (67%) among their patients; they used dogs that already presented severe respiratory and gastric clinical signs, in addition to neurological manifestations typical of the acute phase of distemper.…”
Section: Discussionmentioning
confidence: 95%
“…Although there has been much speculation about the benefits of stem cell therapy canine distemper, and some clinical therapies have been publicized on social networks, few scientific articles have been published. Recently, summaries of several unpublished scientific events and/or studies of interactions between bone marrow cell fractions and stem cells and distemper have appeared, but with few publications in research periodicals involving clinical studies of dogs with canine distemper, such as that of Pinheiro et al (2016),who treated dogs in the acute phase of the disease with MSC, or that by Monteiro (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as doenças neurodegenerativas podemos citar a cinomose canina na qual o vírus é capaz de desmielinizar os neurônios causando uma reação inflamatória no sistema nervoso central, levando a danos irreparáveis aos animais que sobrevivem à doença (Scarpelli 2008). Mais recentemente podemos citar como doença neurodegenerativa a atrofia e degeneração cortical superficial idiopática que assim como na cinomose até o momento não possui tratamento específico, contando apenas com o tratamento paliativo (Cahalan et al 2014, Pinheiro et al 2016. Outro exemplo é a ataxia hereditária canina, sendo considerada uma doença neurodegenerativa ocasionada por mutações e com maior prevalência em animais de raça pura (Urkasemsin 2014).…”
Section: Tópico De Interesse Geralunclassified
“…All flavonoids and phenolic acids demonstrated antiviral action against CDV infection. Other methods of treating CDV infection that have been explored include mesenchymal stem cell therapy [127] and the use of a veterinary pharmaceutical preparation of silver nanoparticles [128].…”
Section: Treatment and Controlmentioning
confidence: 99%